2013
DOI: 10.1007/s00520-013-1880-x
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness-based cognitive group therapy for women with breast and gynecologic cancer: a pilot study to determine effectiveness and feasibility

Abstract: Within the limits of a non-randomized trial, these findings provide preliminary support for the potential psychosocial benefits of MBCT in a heterogeneous group of women with cancer. Future, more comprehensive trials are needed to provide systematic evidence of this therapy in oncology settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 34 publications
0
41
0
2
Order By: Relevance
“…487,527 However, other feasibility and pilot studies using a postal recruitment method have reported similarly low response rates. 547,556,557 Despite the low recruitment rate, retention of participants and questionnaire completion were high and similar between the trial arms, suggesting that randomisation and outcomes assessment were acceptable.…”
Section: Recruitment Retention and Outcomes Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…487,527 However, other feasibility and pilot studies using a postal recruitment method have reported similarly low response rates. 547,556,557 Despite the low recruitment rate, retention of participants and questionnaire completion were high and similar between the trial arms, suggesting that randomisation and outcomes assessment were acceptable.…”
Section: Recruitment Retention and Outcomes Assessmentmentioning
confidence: 99%
“…Studies evaluating group-based interventions in other clinical settings have also reported positive feedback on this format of intervention delivery. 549,557,560 Therefore, although the group format was a reason for non-participation for some patients, those who attended the course enjoyed the format and engagement with other patients. This highlights an issue affecting many trials: a potentially biased sample because of the self-selection of participants with a preference for the intervention.…”
Section: Acceptability Of the Interventionmentioning
confidence: 99%
“…This is particularly so since MBCT participants received an intervention specifically targeting rumination, a cognitive mechanism directly implicated in the relapse of depression [11]. Data from our earlier trial of MBCT [14] showed that improvements in distress, QOL, and mindfulness were maintained 3 months after completion of the intervention; however, comparable data from the MMP are not available. Maintenance of improvement could also not be examined in the review paper [3] referred to above.…”
Section: Discussionmentioning
confidence: 96%
“…From 2010 to 2011, our center piloted an MBCT group program in two rounds of three groups per round among a sample of 42 women with these cancers [14]. This intervention was closely modeled on the original MBCT manual [11] with its focus on daily mindfulness meditation together with targeting the cognitive processes associated with relapse to depression [11] and was adapted for oncology populations by the third author.…”
Section: Introductionmentioning
confidence: 99%
“…En los artículos seleccionados se halló el mindfulness con aplicación a la patología oncológica [7,51,52,53,54,55,56,57,58,59,60,61,62,63], así como su uso en otras patologías crónicas [4,18,64,65]. Se ha demostrado su efecto fisiológico en la reducción de marcadores de ansiedad, como la respuesta humana al cortisol [66,67].…”
Section: Mindfulness (178 %)unclassified